Catalytic Atroposelective Dynamic Kinetic Resolution of Substituted Indoles - Kim, Ahreum; Kwon, Yongseok (Synlett, 2021)
Advances in asymmetric catalysis have led to enormous progress in the atroposelective synthesis of axially chiral biaryls. Because of the biological importance of indoles, stereogenic axes in aryl-substituted indoles have attracted considerable research attention in recent years. Here we present a summary of recent advances in the atroposelective synthesis of aryl-substituted indoles by dynamic kinetic resolution. Although several researchers have developed enantioselective syntheses of 3-arylindoles, N-arylindoles have been much less studied. Accordingly, we have developed a Pictet–Spengler reaction with catalytic and enantioselective control of the axial chirality around the C–N bond of the product. A chiral phosphoric acid induces the cyclization smoothly and with high yields and excellent enantioselectivities. To achieve this high selectivity, an NH group at the ortho-position of the N-substituted aromatic ring that interacts favorably with the catalyst is required. Furthermore, when substituted aldehydes are used instead of paraformaldehyde, both point and axial chiralities can be controlled during the cyclization.1 Introduction2 Atropisomerism in Indoles3 Atroposelective Dynamic Kinetic Resolution of 3-Arylindoles4 Atroposelective Dynamic Kinetic Resolution of N-Arylindoles5 Conclusions
Keywords: arylindoles; atropisomerism; chiral phosphoric acids; dynamic kinetic resolution; Pictet–Spengler cyclization